CELEBRITY ENDORSEMENT TERHADAP MINAT PEMBELIAN - Tyas, Aqidah T W; Bagus, Denny; Lailiyah, Fannisa NK; Ayudhia, Elma; Johan, Ricko; Anggareta, Dewi (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH, 2023)
This study aims to analyze the effect of celebrity endorsement on purchase intention. As well as looking for how the role of Celebrity Endorsement affects consumer buying interest. This study applied the Systematic Literature Review method. Based on the results of a systematic literature review, the researcher found 11 articles, selected for descriptive analysis. The findings found that Celebrity Endorsement affects Purchase Intention